2013
DOI: 10.1007/s00595-013-0765-4
|View full text |Cite
|
Sign up to set email alerts
|

A luteinizing hormone-releasing hormone agonist plus an aromatase inhibitor as second-line endocrine therapy in premenopausal females with hormone receptor-positive metastatic breast cancer

Abstract: The combination of an LHRH agonist plus an AI is a treatment option for premenopausal females with HR-positive MBC that can prolong the chemotherapy-free interval and yield effective disease stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although aminoglutethimide (the first-generation aromatase inhibitor) can suppress the estrogen and inhibit only aromatase enzyme, therefore the levels of circulating androgen were found to be not affected due to suppression of estrogens. In addition, because of the side effects and inconvenience of parenteral administration of the first generation, second, and third generation of the aromatase inhibitors such as anastrozole, formestane and letrozole were developed [ 115 ]. Moreover, the third generation of aromatase inhibitors showed a greater response than tamoxifen treatment alone [ 116 , 117 ].…”
Section: Treatments Of Metastatic Breast Cancermentioning
confidence: 99%
“…Although aminoglutethimide (the first-generation aromatase inhibitor) can suppress the estrogen and inhibit only aromatase enzyme, therefore the levels of circulating androgen were found to be not affected due to suppression of estrogens. In addition, because of the side effects and inconvenience of parenteral administration of the first generation, second, and third generation of the aromatase inhibitors such as anastrozole, formestane and letrozole were developed [ 115 ]. Moreover, the third generation of aromatase inhibitors showed a greater response than tamoxifen treatment alone [ 116 , 117 ].…”
Section: Treatments Of Metastatic Breast Cancermentioning
confidence: 99%
“…No cases of grade 3/4 toxicity were observed. Previous studies have also reportedthat AI combined with LHRH agonist is a safe and well-tolerated treatment, with no serious adverse events[12][13][14][15][16][17][18].…”
mentioning
confidence: 79%
“…Although the benefits of ovarian suppression alone in premenopausal patients with breast cancer is still under investigation, the benefit of combined tamoxifen and LHRH agonist treatment was demonstrated in a meta-analysis of four randomized trials comparing this treatment to LHRH agonist administration alone [19]. Moreover, a few studies have shown promising results for AI in combination with LHRH agonist [12][13][14][15][16][17][18], despite concerns that the use of AI alone in premenopausal women could cause ovarian stimulation [9]. In a pro- Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation